Clitic Misplacement among Normally Developing Children and Children with Specific Language Impairment and the Status of Infl Heads - Petinou, Kakia; Terzi, Arhonto (My University, 2002)
In this article, we focus on an exceptional instance of nonadult positioning of clitics in early Cypriot Greek and Cypriot Greek with specific language impairment (SLI). We attribute misplaced clitics to children's incomplete knowledge concerning properties of the inflectional (Infl) particles, which interact in crucial ways with finite V(erb) movement to M(ood). We claim that children perceive Infl particles as phrasal specifi? ers or adjuncts, unable to check the V-features of M, hence perform V-to-M move? ment even in their presence, and clitics emerge in (nonadult) postverbal position, giving the impression that they have been misplaced. We point out that functional heads seem to be perceived as phrasal in other early languages and possibly also in do? mains other than Infl, and we explain why clitics are not found misplaced in standard Greek and standard Romance, with the exception of Portuguese. Finally, the absence of qualitative differences between the early populations and populations with SLI we studied corroborates with views that consider SLI a language delay, but the degree to which quantitative differences were attested raises questions
Keywords: Clitic misplacement; Specific language impairment; Early Cypriot Greek; Cypriot Greek with specific language impairment (SLI)